Numerical simulation of airflow around a ski jumper during takeoff - Tsubokura, M.; Yamamoto, K.; Onishi, K.; Vuillemin, D.; Wu, G. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Takeoff motion of ski jumping is a transient behavior from in-run to flight posture. Ski jumpers have to perform appropriate takeoff movement leading to the most suitable flight posture to achieve effective aerodynamic forces. However, due to the rapid motion during the take off, the transient aerodynamic forces acting on the ski jumpers are quite difficult to measure and have not yet been fully understood. The final goal of our project is to establish a numerical method based on Computational Fluid Dynamics (CFD) to qualitatively predict the transient aerodynamic forces during the takeoff motion. The objective of this study is to validate the CFD method by using the wind-tunnel measurements conducted by Yamamoto et al.(2013).